ANALYSIS OF STUDENTS’ CRITICAL THINKING SKILLS IN DISCOVERY LEARNING SUPPORTED BY WORDWALL (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2026)
This research utilizing Discovery Learning through Wordwall in order to examine students’ critical thinking level in physics teaching, so that concerning the study of the work and energy. The study employed a quantitative methodology using a one-group pretest posttest design. A sample of 83 tenth graders was selected through purposeful sampling. Data was collected through an essay test developed with Ennis's critical thinking markers. Data were analyzed with descriptive statistics, N-gain, and the Wilcoxon signed-rank test. Results indicate that students' critical thinking skills fall in high to very high range across all variables. The highest achieved was 92.77% for set a strategy and tactics, while provide additional explanation has the lowest of 73.49%. The N gain showed that most of the students in the high (47%) and moderate (34%) categories. The Wilcoxon test confirms a statistical difference between the pretest and posttest data (p < 0.05). The use of Wordwall to support Discovery Learning in class can improve critical thinking, which motivates students and provides more experience during learning. A case study demonstrating how a student centered learning methodology can embed interactive digital media within a more structured educational approach. The results also show that the use of this method can easily become a tool to enhance students' critical thinking skills in terms of physics learning.